Dislodging Dichromate in Mine Slops Applying Flat Supplying Membrane Equipment Containing Carrier N235/7301 - Liang Pei (Membranes, 2022)
A novel flat supplying membrane equipment (FSME) with a sodium hydroxide solution and a mixture of N235/7301 and petroleum has been studied for dislodging dichromate (which can be expressed as Cr (VI) or Cr2O72−) from simulated mine slops. The FSME contained three parts: as a feeding cell, a reacting cell, and a supplying cell. The flat Kynoar membrane was inlaid in the middle of the reacting cell, using the mixed solutions of petroleum and sodium hydroxide, with Tri (octyl decyl) alkyl tertiary amine (N235/7301) as the carrier in the supplying cell and the mine slops with Cr (VI) as the feeding section. The impact parameters of pH and the other ion density in the feeding solutions, the voluminal ratio of petroleum to sodium hydroxide solution and N235/7301 concentration in the supplying solutions were investigated for the obtaining of the optimal technique parameters. It was found that the dislodging rate of Cr (VI) could reach 93.3% in 215 min when the concentration of carrier (N235/7301) was 0.20 mol/L, the voluminal ratio of petroleum and sodium hydroxide in the supplying cell was 1:1, the pH of the feeding section was 4.00, and the Cr (VI) cinit was 3.00 × 10−4 mol/L. The practicability and steadiness of FSME were gained through the exploration of Cr (VI) adsorption on the membrane surface.